Education and Work Future Expectation Scale Adaptation for Indonesian University Students - Dwiastuti, Ike; Hendriani, Wiwin; Andriani, Fitri (Jurnal Kajian Bimbingan dan Konseling, 2023)
The students' optimism about their future careers and education impacts their educational success. The Future Expectation Scale of Adolescents (FESA) can measure future expectations of education and student career. This study aims to adapt the scale of the FESA work and education domain to the Indonesian language and culture. The adaptation in this study follows the six-stage category of the International Commission Test. Development of adaptation items using a forward-backward translation design involving six experts. The comparability of language and content validity assessments involved nine experts. Pilot study for item evaluation involving 15 students from the target population. The quantitative testing was administered to 297 state college students. Results of the comparability assessment of language indicate that the adapted item has a similar structure and meaning. The content validity assessment demonstrates that the adapted item is already relevant, essential, and clear for measuring educational and work expectations. Confirmatory factor analysis (CFA) reveals that this adaptation scale has good construct validity, as indicated by the value of a good fit model that meets the criteria. Reliability based on construct reliability and internal consistency is also good. Thus, the FESA work and education domain scale version for Indonesia is valid and reliable to measure the youth's future expectations of education and work, especially among Indonesian college students.